Behavior of reinforced concrete columns under seismic lateral force and varying axial load - Fan, Yuting (2016)
Column is one of the most important structural elements of a structure. Failure of a column can cause serious consequences. The project is carried out with the intension to study the behavior of reinforced concrete columns subject to simulated seismic horizontal loading and varying axial load. First, an extensive review of previous research on the behavior of reinforced concrete columns is provided. Next, a finite element modeling (FEM) method which can simulate the lateral load-displacement hysteresis loops of reinforced concrete columns under complex loading histories is proposed. The proposed FEM method is utilized to simulate the lateral load-displacement hysteresis loops results from literature for validation. Then, the validated FEM method is employed for parametric study to investigate the effect of varying axial load on the response of reinforced concrete column dominated by flexure, and dominated by shear separately. Finally, the experimentally investigation which involves testing a total of four reinforced concrete specimens under simultaneously cyclic lateral loading and varying axial load is carried out.